(untitled) (Revista científica Olimpia, 2020)
Today in day, we can see in the streets a great quantity of children playing the football in an informal way. The following study, had for objective the one of improving of the features of the knowledge of the internal logic of the football in children football player’s apprentices, starting from the following tactical-strategic foundations: game situations; width and depth in the game space; initiation and finish form of the play. The methods used for the study were the observation, the comparison and inferencial statistical. It was selected in way intentional 12 children with age of six and seven years of the municipality Plaza y Cerro, of Habana. The investigative results demonstrated that the tactical-strategic foundations that were studied should be objective high-priority in the initiation process of the children to the football and they improve applying a strategy that has an active, global and integrated focus, being necessary a bigger time of intervention to achieve significant changes in the individual and collective performance.